Learn and teach: communities of practice as an opportunity for teachers’ professional development - Santos, P. (2017)
Involvement in professional development processes is characteristic of the majority of Portuguese teachers. This situation justifies the need to stir a discussion about the current models of teacher training based on the analysis of requirements and challenges related to social and professional teaching career. For this purpose, our debate focuses on the experience of a project carried out between 2010 and 2011 that confronts current models, most of them steered towards accelerated rehabilitation, with communities of practice among teachers in Portugal. The results presented aim to describe the characteristics of this approach and are based on produced documents and a questionnaire administrated to participating teachers. They also suggest that formed communities of practice pave the road for a professional development that is not individual, competitive or bureaucratic and counteract the attacks made by recent educational policies on some of the traditional pillars of teachers’ professionalism.